Комунікативні наміри дискурсивної стратегії схвалення (на матеріалі англомовного дискурсу) - Гулієва, Діна Олександрівна (Харківський національний університет ім. В. Н. Каразіна, 2014)
У статті подані результати аналізу реалізації комунікативної стратегії схвалення в англомовному дискурсі. Стратегія схвалення визначається як висловлення позитивної оцінки певного об`єкта, особи, дії або ситуації. У дискурсі схвалення втілюється через гіпонімічні стосовно схвалення комунікативні наміри похвали, компліменту, лестощів, захоплення й подяки.

The article presents the results of analyzing the realization of the discursive strategy of approval in the English cinema discourse. The discursive strategy of approval is determined as an expression of a positive assessment of some object, person, action or situation. In discourse approval is realized through its hyponomic communicative intentions of praise, compliment, flattery, admiration, commendation.
The communicative intentions of the discursive strategy of approal (based on the English cinema discourse)
Keywords: сучасна лінгвістика; гармонізація комунікацій; похвала; компліменти; лестощі; захоплення; подяка; communication strategy; communicative intention; approval; praise; compliment; flattery; admiration; commendation